TWO DISTINCT PRECAMBRIAN TERRANES IN THE SOUTHERN PRINCE CHARLES MOUNTAINS, EAST ANTARCTICA: SHRIMP DATING AND GEOCHEMICAL CONSTRAINTS - Mikhalsky E.V.; Beliatsky B.V.; Sheraton J.W.; Roland N.W. (My University, 2006)
The Southern Prince Charles Mountains (SPCM) are mostly occupied by the Archaean Ruker Terrane. The Lambert Terrane crops out in the northeastern part of the SPCM. New geochemical and zircon U-Pb SHRIMP ages for felsic orthogneisses and granitoids from both terranes are presented. Orthogneisses from the Ruker and Lambert terranes differ significantly in their major and trace-element compositions. Those from the Ruker Terrane comprise two distinct groups: rare Y-depleted and abundant Y-undepleted. U-Pb isotopic data provide evidence for tonalite-trondhjemite emplacement at 3392 ± 9 and 3377 ± 9 Ma, pre-tectonic granite emplacement at 3182 ± 9 Ma, metamorphism(?) at c. 3145 Ma, and thermal events at c. 1300(?) and 626 ± 51 Ma. The Lambert Terrane orthogneisses probably originated in a continental magmatic arc. Zircon dating shows a very different geological history: pre-tectonic granitoid emplacement at 2423 ± 18 Ma, metamorphism at 2065 ± 23 Ma, and syn-tectonic granitoid emplacement at 528 ± 6 Ma, syn-tectonic pegmatite emplacement at 495 ± 18 Ma. The Lambert Terrane can be correlated with neither the Meso- to Neoproterozoic Beaver Terrane in the Northern PCM, which differs in isotopic composition, nor with the Archaean Ruker Terrane, which differs in both granitoid chemical composition and the timing of major geological events. It represents a Palaeoproterozoic orogen which experienced strong tectonic re-activation in Pan-African times. The Lambert Terrane has some geochronological features in common with the Mawson Block, which comprises south Australia and some areas in East Antarctica. © 2005 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.
Keywords: ANTARCTICA; GEOCHEMISTRY; ORTHOGNEISS; PRECAMBRIAN; SHRIMP DATING; Precambrian::Archean; Докембрий::Архей